Platelet distribution width as a cost-effective marker for sepsis-associated acute kidney injury: A retrospective cross-section study - Xuelian Yin; Jiebin Li; Enfeng Ren; Yi Zheng; Hong Zhao; Jing Zhang; Qingxia Du (PLoS ONE, 2025)
Background Sepsis-associated acute kidney injury (S-AKI) is a critical complication with high morbidity and mortality. The potential predictive role of platelet distribution width (PDW) in S-AKI remains to be elucidated, and its clinical implications in S-AKI are still not well understood. Objective This study aims to determine whether platelet distribution width within 24 hours of admission could serve as a predictor of S-AKI in septic patients. Method A retrospective analysis of platelet indices in patients with sepsis at the Affiliated Tongren Hospital of Capital Medical University, a tertiary medical center, was conducted from 2015 to 2022. Patients with sepsis were divided into two groups: an S-AKI group and a non-AKI group based on the presence of S-AKI during hospital. Clinical characteristics and laboratory parameters at admission were compared between two groups. A Multivariate logistic regression analysis was conducted to identify risk factors for S-AKI in septic patients. Additionally, receiver operating characteristics (ROC) curve was employed to evaluate the predictive value of these indices for S-AKI in septic patients. Result A total of 410 patients with sepsis were included in the study, including 57 in S-AKI group and 353 in non-AKI group. The levels of PDW and average platelet volume were significantly higher in the S-AKI group compared to those in the non-AKI group. Furthermore, PDW exhibited a positive correlation with SOFA score, APACHE II score, and LDH levels (r = 0.273, r = 0.153, r = 0.233), yielding P-values <0.001, 0.008, and < 0.001 respectively. Multivariate logistic regression analysis identified PDW (OR = 1.324, 95% CI: 1.124–1.559, P = 0.001), SOFA scores (OR = 1.264, 95% CI: 1.011–1.579, P = .040) and LDH (OR = 1.005, 95% CI: 1.002–1.008, P = .002) as independent risk factors for S-AKI in sepsis patients. The area under curve (AUC) values for predicting S -AKI using PDW, SOFA, LDH, and combined SOFA-PDW metrics were found to be approximately equal to 0.696 (95% CI: 0.621–0.771, P = .000), 0.771 (95% CI: 0.706–0.837, P = .000) and 0.695 (95% CI: 0.611–0.780, P = .000), 0.799 (95% CI: 0.739–0.858) respectively. Conclusion PDW values on admission may serve as a useful potential indicator of disease severity and a potential parameter for predicting S-AKI.